Sobre o modelo decolonial: a importância do outro e a urgência de seu olhar - João Alberto Mendonça Silva; Josemar de Campos Maciel; Dolores Pereira Ribeiro Coutinho (Ciências Sociais Unisinos)
This article is an exhibition about changing models of thought intended for Decolonial thinkers, questioning and provoking the massificator system that Latin American societies have lived since the Colonial process. The text is a part of research on development of models based on the promotion of communities and their protagonism, decreasing exogenous interference and promoters of simple speculative profit. Through what is called “Decolonial Turn” we sought to identify how the influence of the metropolis supplanted and replaced ways of being, thinking and doing traditional populations and those who were brought forcibly, characterizing the European pattern of development by capital and accumulation of goods, making them exclusive means of developing. Thus, it points to the proposition that the existence of the figure of the other is underlying the perception of the self, making mutual ontological dependence of these entities for the formation of social being. Finally, the concept of interculturalism brings to the Latin American the reflection of the need for the development by difference, giving voice to the silent, making them visible and protagonist of their journey towards the Good Living.